Pengaruh model pembelajaran tutor sebaya pada keterampilan passing bawah permainan bola voli di SMK Pratama Mulya Karawang - Trian, Dadan; Nugroho, Setio; Purbangkara, Tedi (Jurnal Porkes, 2024)
The purpose of this study was to examine the effect of the peer tutor learning model on the lower passing skills of volleyball games. This research is quantitative research with experimental methods and uses a one group pretest-posttest design. The population of all grade XI SMK Pratama Mulya Karawang amounted to 190 students. The sampling technique used cluster random sampling and the sample size was 76 students. The instrument used is the skill of lower passings in volleyball games. The results of the analysis obtained descriptive text experiment posttest data obtained from test scores. The value obtained was the lowest 13, the highest 16, an average of 14.53 and a standard deviation of 1.033. The output of “mann-whitny test” is known asymp sig value. (2-tailed) is 0.000 <0.05, so the hypothesis is accepted. So it can be concluded that there is an average difference between the pretest and posttest results which means that there is an effect of the peer tutor model on the lower passing skills of volleyball games for class XI students of SMK Pratama Mulya.